Public Perception Toward Oil Palm-Based Entomotourism Development in Carey Island Sime Darby EcoGardens - Nazhirah, Ain; Awg Abd Rahman, Aqilah (Enhanced Knowledge in Sciences and Technology, 2024)
Oil palm-based entomotourism is an innovative blend of agriculture and ecotourism, offering a unique experience by showcasing the biodiversity within and around oil palm plantations. This emerging form of tourism invites visitors to explore insect life amidst sustainable agricultural practices. Entomotourism, a niche tourism sector focusing on insect-related activities, has gained attention in the context of sustainable development. This study determine the diversity of insects species in Carey Island Sime Darby EcoGarden. This study investigates public perceptions regarding the development of oil palm-based entomotourism in Carey Island's Sime Darby EcoGarden. The research aims to understand how individuals perceive the integration of oil palm plantations and entomotourism initiatives. The study employs qualitative and quantitative methods to analyze public attitudes, concerns, and expectations surrounding this unique form of eco-friendly tourism.